Bleach Plant Effluents from the Pulp and Paper Industry - Bajpai, Pratima; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
This book covers bleach plant effluents- the most polluting effluent from the pulp and paper industry. Some of the consequences of the disposal of bleach effluents into surface waters include- disappearance of benthic invertebrates, a high incidence of fish diseases, and mutagenic effects on the aquatic fauna. This book describes the environmental impact of bleach plant effluents, environmental regulations, and measures to reduce the pollution load by internal process modification and external treatments.
Background -- Pulp and Paper making process -- Pulp Bleaching and Bleaching effluents -- Environmental effects on bleach plant effluents -- Strategies used for reducing the generation of pollutants -- External treatments -- Conclusions and future perspectives -- References.
Keywords: Chemistry; Textile industry; Chemical engineering; Environmental chemistry; Waste disposal; Chemistry; Textile Engineering; Waste Management/Waste Technology; Industrial Chemistry/Chemical Engineering; Environmental Chemistry